Vitamin E and Silymarin Reduce Oxidative Tissue Damage during Gentamycin-Induced Nephrotoxicity - Tsvetelin Georgiev; Galina Nikolova; Viktoriya Dyakova; Yanka Karamalakova; Ekaterina Georgieva; Julian Ananiev; Veselin Ivanov; Petya Hadzhibozheva (MDPI AG, 2023)
Aminoglycoside antibiotics and gentamicin (GN), in particular, are still widely used in clinical practice. It is a well-known fact that GN causes nephrotoxicity, and redox disturbances are discussed as a factor in its side effects. Recently, a new type of cell oxidative death, named ferroptosis, was discovered; it is associated with iron accumulation in the cell, glutathione (GSH) depletion and inactivation of glutathione peroxidase-4 (GPX4), reactive oxygen species (ROS) increment with concomitant lipid peroxidation. In this regard, a possible connection between GN-induced renal damage, ferroptosis and the overall antioxidant status of the organism could be investigated. Moreover, due to its beneficial effects, GN is still one of the main choices as a therapeutic agent for several diseases, and the possible reduction of its side effects with the application of certain antioxidants will be of important clinical significance. The study was conducted with adult male white mice divided into several groups (n = 6). GN nephrotoxicity was induced by the administration of GN 100-200 mg/kg i.p. for 10 days. The control group received only saline. The other groups received either Vitamin E (400 mg/kg p.o.) or Silymarin (200 mg/kg p.o.) applied alone or together with GN for the same period. After the end of the study, the animals were sacrificed, and blood and tissue samples were taken for the assessment of biochemical parameters and antioxidant status, as well as routine and specific for GPX4 histochemistry examination. The experimental results indicate that GN-induced nephrotoxicity negatively modulates GPX4 activity and is associated with increased production of ROS and lipid peroxidation. The groups treated with antioxidants demonstrated preserved antioxidant status and better GPX4 activity. In conclusion, the inhibition of ROS production and especially the suppression of ferroptosis, could be of clinical potential and can be applied as a means of reducing the toxic effects of GN application.